2018
DOI: 10.3233/nre-182536
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of sleep after traumatic brain injury

Abstract: Sleep-wake disturbances (SWD) are prevalent in the traumatic brain injury (TBI) population and may exacerbate related neurobehavioral impairments. As such, it is important to recognize and treat SWD early to allow for optimal cognitive recovery following a TBI. A number of medications are currently available for treatment of SWD. However, most research in this area has historically focused on neurologically intact populations. This article reviews key pharmacologic treatment principles and agents to consider f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…One randomized controlled trial in adults comparing melatonin to amitriptyline found melatonin improved daytime alertness compared to controls, but no alterations in sleep latency or duration were observed [ 34 , 146 ]. Additionally, one RCT found a 4-week supplementation regimen to be safe and effective for improving sleep quality in patients with prior TBI [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…One randomized controlled trial in adults comparing melatonin to amitriptyline found melatonin improved daytime alertness compared to controls, but no alterations in sleep latency or duration were observed [ 34 , 146 ]. Additionally, one RCT found a 4-week supplementation regimen to be safe and effective for improving sleep quality in patients with prior TBI [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quetiapine may also be effective in managing aggressive behaviour [74], whilst propranolol, methylphenidate and valproic acid may also be helpful in managing agitation [72]. Benzodiazepines are not recommended due their negative effect on neurological recovery and high incidence of adverse effects [73].Trazodone is often used to manage insomnia, although there is little research in its use in patients with TBI [75].…”
Section: Rehabilitationmentioning
confidence: 99%
“…Benzodiazepines are not recommended due their negative effect on neurological recovery and high incidence of adverse effects [73]. Trazodone is often used to manage insomnia, although there is little research in its use in patients with TBI [75]. Tools such as the agitated behavioural scale can be used as a serial measure of changes in behaviours over time.…”
Section: Rehabilitationmentioning
confidence: 99%